2011
DOI: 10.1088/1741-2560/8/1/014001
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4-ethylenedioxythiophene) (PEDOT) polymer coatings facilitate smaller neural recording electrodes

Abstract: We investigated using poly(3,4-ethylenedioxythiophene) (PEDOT) to lower the impedance of small, gold recording electrodes with initial impedances outside of the effective recording range. Smaller electrode sites enable more densely packed arrays, increasing the number of input and output channels to and from the brain. Moreover, smaller electrode sizes promote smaller probe designs; decreasing the dimensions of the implanted probe has been demonstrated to decrease the inherent immune response, a known contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
206
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(218 citation statements)
references
References 41 publications
12
206
0
Order By: Relevance
“…These results show that a single-cell-scale electrode has the ability to both record and chemically stimulate, demonstrating the local effects of therapeutic treatment, and opening a range of opportunities in basic neuroscience as well as medical technology development. one order of magnitude lower than bare Au, Pt, and Ir electrodes of similar dimensions at 1 kHz), with the low impedance being attributed partly to the high porosity, giving an increased electrochemical surface area (12)(13)(14). Additionally, with their mixed electronic and ionic conductivity and the soft mechanical properties that match those of the neural tissue, conducting polymers are ideally suited to obtain high signal-to-noise ratio recordings at the neural interface (15,16).…”
Section: Significancementioning
confidence: 99%
“…These results show that a single-cell-scale electrode has the ability to both record and chemically stimulate, demonstrating the local effects of therapeutic treatment, and opening a range of opportunities in basic neuroscience as well as medical technology development. one order of magnitude lower than bare Au, Pt, and Ir electrodes of similar dimensions at 1 kHz), with the low impedance being attributed partly to the high porosity, giving an increased electrochemical surface area (12)(13)(14). Additionally, with their mixed electronic and ionic conductivity and the soft mechanical properties that match those of the neural tissue, conducting polymers are ideally suited to obtain high signal-to-noise ratio recordings at the neural interface (15,16).…”
Section: Significancementioning
confidence: 99%
“…Recent studies show the same effect for CPs. Ludwig et al reported on an about 10-fold decrease in impedance at 1 kHz for electrochemically deposited PEDOT coatings on Ø 15 µm Au recording electrodes, which reduced noise levels by about half (Ludwig et al, 2011). In earlier studies, the same effect was demonstrated for polypyrrole (PPy) (Cui et al, 2001).…”
Section: Electrode Functionalization and Post-processing Strategiesmentioning
confidence: 76%
“…They decrease interfacial impedance and increase the charge capacity of the electrode. One example is poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS),which was found to increase the SNR for in-vivo implanted electrodes [72]. We found that PEDOT:PSS deposited on Au electrodes using the methods outlined in [71] resulted in a decrease in impedance of nearly two orders of magnitude [51].…”
Section: E Interfacial Impedancementioning
confidence: 97%